PENGEMBANGAN POJOK BACA DI SDN 1 UREK-UREK UNTUK MENINGKATKAN LITERASI MEMBACA - Diyah Ayu Widyaningrum; As’ad Syamsul Arifin; Rina Wijayanti (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Indonesia has a low interest in reading, so reading literacy is also low. The observation results from the Teaching Campus team Batch 3 at SDN 1 Urek-urek showed that there was no library there yet, so students were not used to reading. The absence of library facilities can be overcome through the establishment of a reading corner. The reading corner is a reading area located in a corner. This type of research is descriptive research. Data collection techniques through observation, interviews and documentation. The results showed that most students responded positively to the establishment of a reading corner. There is an effort from the teacher to increase interest in reading and improve the reading corner.